Hidrodinâmica nos canais que conectam o Rio Amazonas e o Canal Pará - Baltazar, Laíssa Régia Sarmento (2019)
Estuaries systems often have complex channels patterns subject to tidal forcing from different entrances. Many researches have been relating that the flows through multi-channel are controlled by the magnitude and phase of tidal forcing and how the tides influence river discharge division over distributaries. The Amazon River and Para channel are connected by a complex channel network and join two large estuarine systems and different hydrologic basins located at North of Brazil. The main hydrodynamic forcings are the large discharge of Amazon River and the macro-tides entering from the ocean, converging along the multichannels. This research used data and numerical model to analyze the tidal behavior along the two main connecting channels: Tajapuru and Breves. The analysis of the phase of M2 component pointed the tidal convergence zone, which did not show changes with Amazon River seasonality. Results of water levels and velocities pointed a more progressive tidal wave propagating from the Amazon South channel towards the Para channel. A more standing tidal wave behavior is shown for the tidal wave propagating from the Para channel up to the convergence zone. Residual flow is consistently directed from Amazon South channel towards Para channel. It is shown that the main factor influencing this exporting flow is the Amazon River seasonality. However, the tidal effect is important, especially the fluxes due the asymmetries (compound M4) and non linear interactions (compound Msf).